Cyclotron resonance of electrons and holes in graphene monolayers. - Chuang, K; Deacon, R; Nicholas, R; Novoselov, K; Geim, A (2008)
We report studies of cyclotron resonance in monolayer graphene. Cyclotron resonances are detected by observing changes in the photoconductive response of the sample. An electron velocity at the Dirac point of 1.093 x 10(6) m s(-1) is obtained, which is the fastest velocity recorded for all known carbon materials. In addition, a significant asymmetry exists between band structure for electrons and holes, which gives rise to a 5% difference between the velocities at energies of 125 meV away from the Dirac point.